Clinical utilisation of implantable loop recorders in adults with Fabry disease—a multi-centre snapshot study - Roy, Ashwin; Vijapurapu, Ravi; Kurdi, Hibba; Orsborne, Christopher; Woolfson, Peter; Kalla, Manish; Jovanovic, Ana; Miller, Christopher A.; Moon, James C.; Hughes, Derralynn A.; Geberhiwot, Tarekegn; Steeds, Richard P. (Frontiers in Cardiovascular Medicine, 2023)
Fabry disease (FD) is an X-linked deficiency of alpha-galactosidase A, leading to lysosomal storage of sphingolipid in multiple organs. Myocardial accumulation contributes to arrhythmia and sudden death, the most common cause of FD mortality.There is a need for risk stratification and prediction to target device therapy.Implantable loop recorders (ILR) allow for continual rhythm monitoring up to 3 years.We performed a retrospective study to evaluate current ILR utilisation in FD and quantify arrhythmia burden detected resulting in therapy change. This was a snapshot assessment of 915 patients with FD across 3 specialist centres in England between 1/1/2000 and 1/9/2022. In total, 22 (2.4%) patients underwent clinically indicated ILR implantation. Mean implantation age was 50 years and thirteen (59%) were female.Following implantation, nine (41%) patients had arrhythmia detected requiring intervention (six on ILR and three post-ILR battery depletion). Three sustained atrial high-rate episodes and were commenced on anticoagulation. Three had nonsustained tachyarrhythmia and were commenced on beta blockers. Post ILR battery depletion, one had complete heart block and two had sustained ventricular tachycardia, all requiring device therapy. Those with arrhythmia had a shorter PRinterval on electrocardiography. This study demonstrates that ILR implantation in FD undercovers a high burden of arrhythmia. ILRs are likely to be under-utilised in this pro-arrhythmic cohort, perhaps restricted to those with advanced FD cardiomyopathy.Following battery depletion, ongoing vigilance and arrhythmia-surveillance is advised given those suffering major arrhythmic events post-ILR monitoring. Further work is required to establish who would benefit most from implantation.